Qur’anic Reading Skills Development Through Love-Based BTQ Learning: Peningkatan Kemampuan Membaca Al-Qur’an Melalui Pembelajaran BTQ Berbasis Cinta - Fajar Shadiq; Hamka Ilyas; Saprin Saprin (Academia Open, 2026)
General Background: Qur’anic literacy is a core foundation of Islamic education in pesantren, where reading accuracy and spiritual engagement are inseparable learning objectives. Specific Background: The implementation of Kurikulum Merdeka introduces flexible, student-centered learning principles that must be harmonized with traditional pesantren practices, particularly in Baca Tulis Al-Qur’an (BTQ) instruction. Knowledge Gap: Limited empirical studies have explored how Kurikulum Merdeka can be contextually adapted within pesantren culture through a love-based pedagogical approach to strengthen Qur’anic reading competence. Aims: This study aims to analyze the implementation of love-based BTQ learning within the framework of Kurikulum Merdeka in improving students’ Qur’anic reading skills at Pondok Pesantren Manahilil Ulum DDI Kaballangang, Pinrang. Results: Using a qualitative descriptive approach through observation, interviews, and documentation, the findings show improvements in makhraj accuracy, tajwid application, and reading fluency, supported by humanistic teacher modeling, emotional closeness, differentiated instruction, and structured daily reading habituation. Novelty: This study highlights the integration of Kurikulum Merdeka with a pesantren-based love-centered learning model that combines traditional methods such as sorogan and tahsin with adaptive curricular principles. Implications: The findings provide a contextual framework for pesantren to develop BTQ learning that aligns curricular flexibility with spiritual values, contributing to sustainable Qur’anic literacy development within Islamic boarding schools. Highlights • Improved Qur’anic reading accuracy through structured tahsin and daily habituation• Humanistic teacher modeling strengthened students’ confidence and spiritual engagement• Curriculum flexibility supported differentiated BTQ learning within pesantren culture Keywords Kurikulum Merdeka; Baca Tulis Al-Qur’an; Pesantren Education; Qur’anic Literacy; Love-Based Learning